Courting Economic Development - Brown, James R.; Cookson, J. Anthony; Heimer, Rawley Z. (Published by Oxford University Press on behalf of the World Bank, 2019)
The authors show that court enforcement uncertainty hinders economic development using sharp variation in judiciaries across Native American reservations in the United States. Congressional legislation passed in 1953 assigned state courts the authority to resolve civil disputes on a subset of reservations, while tribal courts retained authority on unaffected reservations. Although affected and unaffected reservations had similar economic conditions when the law passed, reservations under state courts experienced significantly greater long-run growth. When the authors examine the distribution of incomes across reservations, the average difference in development is due to the lower incomes of the most impoverished reservations with tribal courts. The authors show that the relative underdevelopment of reservations with tribal courts is driven by reservations with the most uncertainty in court enforcement.